Gaya Bahasa Pertentangan dalam Novel Perahu Kertas Karya Dewi Lestari - Inda Puspita Sari (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
The purpose of this study was to describe the contradictory language style found in the Perahu Kertas novel by Dewi Lestari. This study used a descriptive qualitative research method for Dewi Lestari's novel paper boat as the data source. Data collection techniques in this study with library techniques, refer technique, and note. Data analysis techniques begin with data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the analysis of the Perahu Kertas novel that has been done, it is known that there are opposing language styles that are dominated by the use of hyperbolic language styles and are equipped with litotes, oksimoron, paranomasia, ivendo, climax, anticlimactic, sarcasm, antiphasis, paradox, irony, cynicism. and hyperbaton. The contradictory language style created by Dewi Lestari in the Perahu Kertas novel shows that the game of using language styles is very important in building a novel.